1997
DOI: 10.1038/sj.cdd.4400293
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate- but not TGFβ1-induced apoptosis of colorectal adenoma cells is associated with increased expression of the differentiation markers E-cadherin and alkaline phosphatase

Abstract: Sodium butyrate and transforming growth factor b (TGFb 1 ) are growth inhibitory to colonic adenoma cell lines. Butyrate induces apoptosis, whereas in some adenoma cell lines, TGFb 1 can be growth inhibitory without apoptosis. In this report, we show that the adenoma cell line PC/BH/C1 undergoes apoptosis in response to TGFb 1 . Butyrate induced cell death is preceded by the induction of two markers of colonic differentiation ± alkaline phosphatase (ALP) activity and E-cadherin protein expression. However, TGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…On treatment with NaBt, an analogous level of induction of both differentiation markers (ALP and E-cadherin) was detected in both adenoma-and carcinomaderived cell lines, indicating that an increase in differentiation was detectable in all cell lines (the tumorigenic cell lines PC/AA/C1/SB10 and PC/JW2 as well as the non-tumorigenic PC/AA/C1, S/RG/C2 cells) (Butt et al, 1997). Additionally it has been established using FACs analysis that the G 1 /S ratio increases in a dose-dependent manner in the colorectal cell lines used in our study after 48 hours of NaBt treatment (approximately 1.5-3.2 fold, depending on cell line; Butt, 1996). Therefore the PC/AA/C1 adenoma cells and their tumorigenic derivative PC/AA/C1/SB10 cells were treated with doses of sodium butyrate (0-3 mM for 48 hours) which had previously been shown to induce differentiation, and the Rb protein expression determined by Western analysis.…”
Section: Treatment With the Differentiation Agent Sodium Butyrate Resmentioning
confidence: 84%
See 2 more Smart Citations
“…On treatment with NaBt, an analogous level of induction of both differentiation markers (ALP and E-cadherin) was detected in both adenoma-and carcinomaderived cell lines, indicating that an increase in differentiation was detectable in all cell lines (the tumorigenic cell lines PC/AA/C1/SB10 and PC/JW2 as well as the non-tumorigenic PC/AA/C1, S/RG/C2 cells) (Butt et al, 1997). Additionally it has been established using FACs analysis that the G 1 /S ratio increases in a dose-dependent manner in the colorectal cell lines used in our study after 48 hours of NaBt treatment (approximately 1.5-3.2 fold, depending on cell line; Butt, 1996). Therefore the PC/AA/C1 adenoma cells and their tumorigenic derivative PC/AA/C1/SB10 cells were treated with doses of sodium butyrate (0-3 mM for 48 hours) which had previously been shown to induce differentiation, and the Rb protein expression determined by Western analysis.…”
Section: Treatment With the Differentiation Agent Sodium Butyrate Resmentioning
confidence: 84%
“…The short-chain fatty acid sodium butyrate (NaBt), a natural fermentation product of dietary fibre (Cummings, 1981) has been found to induce differentiation in a number of different cell types including colonic cells (Leder and Leder, 1975;Prasad and Sinha, 1976). Furthermore, it has previously been established that NaBt can induce differentiation in colorectal cell lines, and this induction of differentiation is evidenced by increased expression of the differentiation markers alkaline phosphatase (ALP) and E-cadherin (Butt et al, 1997). On treatment with NaBt, an analogous level of induction of both differentiation markers (ALP and E-cadherin) was detected in both adenoma-and carcinomaderived cell lines, indicating that an increase in differentiation was detectable in all cell lines (the tumorigenic cell lines PC/AA/C1/SB10 and PC/JW2 as well as the non-tumorigenic PC/AA/C1, S/RG/C2 cells) (Butt et al, 1997).…”
Section: Treatment With the Differentiation Agent Sodium Butyrate Resmentioning
confidence: 99%
See 1 more Smart Citation
“…The b-catenin/Tcf-4 pathway is considered to be the most important one controlling the switch between cellular differentiation and proliferation in intestinal epithelial cells. Induction of differentiation in HT29 cells by butyrate was observed to be accompanied by the upregulation of p21 and p53 [19]. In another study, the relationship between butyrate-mediated growth inhibition and induction of a more differentiated phenotype was investigated in a set of adenoma-derived cell lines.…”
Section: Discussionmentioning
confidence: 96%
“…We found that RNA interference-mediated inhibition of vimentin expression resulted in reemergence of keratin gene expression in cell culture and the production of smaller, more differentiated tumors in athymic mice, suggesting potential for development as a treatment modality. Pharmacology-based differentiation therapies have been developed by others, including the use of retinoids (46 -48) and butyrates (49). Combination therapy of retinoid acid receptor and retinoid X receptor agonists with chemotherapeutic drugs has shown some promise clinically in the treatment of lung cancer (50).…”
Section: Discussionmentioning
confidence: 99%